Clinical application of the CO2 laser in Ab externo Schlemm's canal surgery - Zhang, Liu; Yao, Yihua; Lin, Qingxia; Li, Yanhong; Zhang, Jianhui (Frontiers in Medicine, 2022)
Purpose: This study aimed to investigate the clinical application of laser as a knife in Ab externo Schlemm’s canal (SC) surgery and compare the efficacy and safety of the CO2 laser with the conventional procedure using a surgical knife. Methods: Patients who underwent either canaloplasty and trabeculotomy with CO2 laser system which was used to locate and ablate the outer wall of SC at the time interval between May 2020 and May 2021 were identified, their medical files were reviewed, and their results were compared with conventional surgery group with conventional surgical knife at the same time period. The following datas were conducted and compared: age, sex, intraocular pressure (IOP), number of drugs, best-corrected visual acuity (BCVA), mean deviation and pattern standard deviation of visual field examination. Results: A total of 49 patients (49 eyes) were included in this study, including 23 in the Laser surgery group and 23 in the conventional surgery group. Canal opening time was 49.33 ± 25.23 s and 116.50 ± 31.79 s for laser surgery group and conventional surgery group, respectively. This difference between the two groups was statistically significant (P < 0.01). Haemorrhage occurred in 5 eyes during ablation for the laser surgery group and in 24 eyes for the conventional surgery group. In addition, anterior chamber penetration occurred in 2 cases for the laser surgery group and in 6 cases for the conventional surgery group. The success rate of identifying and opening outer wall of SC was 91.30% (21 eyes) for the laser surgery group and 76.92% (20 eyes) for the conventional surgery group. The difference between preoperative and postoperative intraocular pressure for each group was statistically significant (P < 0.01), and there were no statistically significant differences across the two groups in terms of postoperative IOP and BCVA (P > 0.05). Conclusion: Compared with the conventional procedure using a surgical knife, CO2 laser-assisted ablation of the outer wall of SC was less time-consuming and less technically challenging. CO2 laser-assisted ablation also resulted in fewer complications. Furthermore, it had a shorter learning curve and a higher success rate of identifying and opening SC.